2009
DOI: 10.1371/journal.pone.0007815
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Genetically Monomorphic Bacteria: DNA Sequencing in Mycobacterium tuberculosis Highlights the Limitations of Current Methodologies

Abstract: Because genetically monomorphic bacterial pathogens harbour little DNA sequence diversity, most current genotyping techniques used to study the epidemiology of these organisms are based on mobile or repetitive genetic elements. Molecular markers commonly used in these bacteria include Clustered Regulatory Short Palindromic Repeats (CRISPR) and Variable Number Tandem Repeats (VNTR). These methods are also increasingly being applied to phylogenetic and population genetic studies. Using the Mycobacterium tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
449
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(473 citation statements)
references
References 71 publications
19
449
2
3
Order By: Relevance
“…Thus, MIRU 39 should be included in the MIRU-VNTR typing protocol for the south Indian strains where EAI isolates correspond to 84 % of the total circulating strains (Shanmugam et al, 2011). Our findings also suggest that the MIRU polymorphism may vary among geographically diverse clinical isolates, so regionspecific MIRU locus standardization will be necessary to achieve a high discriminatory index as reported previously (Comas et al, 2009). Here, we demonstrated that MIRU 39 occupying the intergenic region between Rv3870 and Rv3871 is present in variable copy numbers ranging from one to six.…”
Section: Rd-inssupporting
confidence: 57%
“…Thus, MIRU 39 should be included in the MIRU-VNTR typing protocol for the south Indian strains where EAI isolates correspond to 84 % of the total circulating strains (Shanmugam et al, 2011). Our findings also suggest that the MIRU polymorphism may vary among geographically diverse clinical isolates, so regionspecific MIRU locus standardization will be necessary to achieve a high discriminatory index as reported previously (Comas et al, 2009). Here, we demonstrated that MIRU 39 occupying the intergenic region between Rv3870 and Rv3871 is present in variable copy numbers ranging from one to six.…”
Section: Rd-inssupporting
confidence: 57%
“…Contrary to other common markers, such as Spoligotypes, VNTRs or RFLPs, SNPs are found in many sites across the MTBC genomes (in the order of tens of thousands) and can easily preserve traces of the evolutionary background of a sample (Comas et al, 2009). Furthermore, the evolutionary dynamics of MTBC species are particularly benficial for SNP-based phylogenetic analyses: on one hand, the substitution rate of MTBC is considerably low compared to other bacteria, which reduces the chance of convergent evolution in the absence of selection (Achtman, 2008); on the other hand, horizontal gene transfer has very limited expression in MTBC, reducing further the chance of phylogenetic inconguences.…”
Section: Discussionmentioning
confidence: 99%
“…Spoligotyping has been shown not to be reliable for phylogenetic analysis, because its patterns may not reflect the evolution history of a strain and the "signature" pattern of the strain groups can be ambiguous or uninformative (Comas et al, 2009). To circumvent these problems we used a novel software that relies on an extensive Spolygotype database to assign new Spoligotype patterns to strain groups (SPOTCLUST, Vitol et al, 2006).…”
Section: Strain Identification Using Snps Vs Spoligotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…This reinforces the observation that first-line typing schemes for different countries may require the use of different loci because the population structures of circulating M. tuberculosis strains vary across different parts of the world . Moreover, the relative discriminatory powers of particular VNTR loci vary depending on the strain in question (Murase et al 2008, Comas et al 2009). …”
Section: Discussionmentioning
confidence: 99%